Natural products based on Correa's cascade for the treatment of gastric cancer trilogy: Current status and future perspective - Wenhao Liao; Jing Wang; Yuchen Li (Journal of Pharmaceutical Analysis)
Gastric carcinoma (GC) is a malignancy with multifactorial involvement, multicellular regulation, and multistage evolution. The classic Correa's cascade of intestinal GC specifies a trilogy of malignant transformation of the gastric mucosa, in which normal gastric mucosa gradually progresses from inactive or chronic active gastritis (Phase I) to gastric precancerous lesions (Phase II) and finally to GC (Phase III). Correa's cascade highlights the evolutionary pattern of GC and the importance of early intervention to prevent malignant transformation of the gastric mucosa. Intervening in early gastric mucosal lesions, i.e., Phase I and II, will be the key strategy to prevent and treat GC. Natural products (NPs) have been an important source for drug development due to abundant sources, tremendous safety, and multiple pharmacodynamic mechanisms. This review is the first to investigate and summarize the multi-step effects and regulatory mechanisms of NPs on the Correa's cascade in gastric carcinogenesis. In phase I, NPs modulate Helicobacter pylori urease activity, motility, adhesion, virulence factors, and drug resistance, thereby inhibiting H. pylori-induced gastric mucosal inflammation and oxidative stress, and facilitating ulcer healing. In Phase II, NPs modulate multiple pathways and mediators regulating gastric mucosal cell cycle, apoptosis, autophagy, and angiogenesis to reverse gastric precancerous lesions. In Phase III, NPs suppress cell proliferation, migration, invasion, angiogenesis, and cancer stem cells, induce apoptosis and autophagy, and enhance chemotherapeutic drug sensitivity for the treatment of GC. In contrast to existing work, we hope to uncover NPs with sequential therapeutic effects on multiple phases of GC development, providing new ideas for gastric cancer prevention, treatment, and drug development.